حكم أخذ اللقاحات ودور الدولة في الإلزام به :لقاح كورونا 19 أنموذجًا: Provision of Taking Vaccines and the Role of the Government on making it Mandatory: Covid-19 Vaccine as a Model - Mohamed El Shehab, Abeer Jassim (Online Journal of Research in Islamic Studies, 2022)
Research Objectives: The research aims to discuss the issue of the state obligating its members to vaccinate, both by root and download, and then the first topic came to clarify the reality of the Corona vaccine and the treatment with it, and the related provisions. Then the second topic came in the ruling on obligating its citizens to be vaccinated with vaccines - the Corona 19 vaccine as a model; In it, I dealt with the rooting of the rule of the state obligating its subjects to be vaccinated and the opinions of the jurists on it, and its basis from the legal evidence, the principles of jurisprudence and legal policy, and what is related to this from the jurisprudence of the purposes and its application on the descending side by verifying its principles, which helps in conceptualizing the issue and giving it the appropriate ruling within the interest consideration. Study Methodology: This research followed the inductive approach, collecting evidence of the issue from the Qur’an, the Sunnah, the rules and legal purposes, and the analytical approach to the jurisprudential trends and the extent of the imam’s authority to compel according to his reformist view and the rules governing it. Results: One of the most prominent results is that the guardian or his representative may compel his flock to be vaccinated in order to prevent the emerging disease of Corona Covid-19; To ward off the spoilage of the spread of deadly diseases and epidemics, and to bring the interest of the members of society to preserve their lives, and based on evidence from the Qur’an and Sunnah and the overall purposes and the rules of jurisprudence and fundamentalism. The originality of the research: The scientific value of the research appears in highlighting the political interest in the extent of the imam’s authority in obligating receiving vaccinations, as well as that it highlights the role of the jurist in keeping pace with developments by combining the medical, jurisprudential and political aspects.